(untitled) (Research, Society and Development, 2021)
Robotic surgery is a minimally invasive technology with the need for specific training and knowledge of the clientele to operationalize this resource. In-depth knowledge of this reality and the determining factors of clinical and procedural aspects in training hospitals is necessary. The study aimed to identify the surgical profile of patients undergoing robotic surgery at a university hospital. As a methodology, this is a retrospective study, with a descriptive quantitative approach. Data collection was based on the medical records of users assisted by the robotic surgery team, from July to December 2019. The results showed that 139 procedures were performed, with urological surgery being the main robotic specialty (61.2%), in men (64.7%) between 60 and 69 years old (43.2%), ASA 2 (77.7%) and hypertension the most frequent risk factor (46.8%). Robotic surgery uses general anesthesia (91.3%) with an average time of 2 to 4 hours of surgery (43.2%) and 4 to 6 hours under anesthetic effect (57.5%). The Trendelemburg position associated with the lithotomy occurred in most surgeries (45.3%) with an ELPO scale with a score greater than or equal to 20 (52.5%). Capnography is essential (95.7%) in addition to peripheral venous access (97.9%), with perioperative complications being the difficult airway (2.9%), although the scores are low according to international data. Conclusion: The data obtained in this study allowed to identify the profile of this clientele, offering a basis for the health team to act according to the surgical specificity.